Management of recurrent peripheral giant cell granuloma -a case report - Prathypaty, Santha Kumari; Potharaju, Santhi Priya; Chintala, Ravi Kanth; Guvvala, Satheesh Kumar; Kolliboyana, Jai Krishna Srikanth (International Journal of Health, 2016)
Peripheral giant cell granuloma (PGCG) which is also called as Giant cell Epulis is one of the most common reactive hyperplastic lesions of the oral cavity. There are various etiologies relating PGCG which include local irritation, trauma, tooth extraction, irregular restorations, plaque, calculus, chronic infection & impacted food. One important other etiology of this benign tumor is its origin from periosteum or periodontal membrane. Excision of the lesion completely along with extraction of involved tooth is the option of treatment to prevent recurrence of the lesion in some cases. This case report describes the recurrence of the Peripheral giant cell granuloma even after complete excision in 3 months.Management of recurrent Peripheral giant cell granuloma by surgical excision of the lesion was carried out along with extraction of the associated tooth and curettage of the bone walls. Profuse bleeding after tooth extraction was managed by gel-spun. Periodic recalls doesn’t show any recurrence until one month.